Karakteristik Umbi Plasma Nutfah Tanaman Talas (Colocasia esculenta) - Mamik Setyowati; Ida Hanarida; nFN Sutoro (Buletin Plasma Nutfah, 2007)
Taro have been cultivated and consumed as a food supplement in Indonesia. Beside it used as a food, it is also as source of industrial purposes, such as a part of raw material of cosmetic or plastic. Characteristic of tuber (corm) of taro determine their usage. Utilization of germplasm collection of taro could be done more intensively by studying their morphological characters. Experiment was conducted in 2005 consisted of 170 accessions of taro. Morphological characters of tuber have been observed at harvest time. Result of the study show that variability of morphological characters were exist within areas or among areas. There are several interesting varieties which have long umbi or high tuber yield and specific tuber flesh color. AbstrakTanaman talas telah lama dibudidayakan dan dimanfaatkan sebagai sumber pangan tambahan di Indonesia. Di samping sebagai sumber pangan, talas juga dapat dimanfaatkan untuk keperluan industri, misalnya sebagai bahan baku kosmetik dan plastik. Karateristik umbi talas menentukan penggunaannya. Pemanfaatan talas dapat ditingkatkan dengan mempelajari sifat-sifat morfologi yang dimiliki plasma nutfah yang telah dikoleksi. Percobaan dilaksanakan pada tahun 2005 terdiri atas 170 aksesi plasma nutfah talas. Karakter morfologi umbi diamati setelah panen. Hasil penelitian menunjukkan bahwa terdapat keragaman karakter morfologi dalam daerah atau antar daerah asal plasma nutfah. Dari koleksi plasma nutfah yang telah dimiliki diperoleh aksesi yang menarik seperti umbi talas yang panjang dengan warna daging umbi yang khas.